USATF high peformance plan:overview of new sport science initiatives- distance events - Chapman, R. F. (Track Coach, 2015)
At the beginning of each quadrennium, USA Track & Field presents a copy of a four-year High Performance Plan to the U.S. Olympic Committee for their consideration and support. As part of the 2013-2016 USATF High Performance Plan, five new sports science initiatives (broadly referred to below as the Initiatives), were introduced and outlined. Each of these proposed Initiatives are believed to carry the potential of a positive impact in medal production in 2016-either by increasing medal wins in event areas where the USA was lacking in 2012, or by defending medal winning event areas from 2012. As a continuing contribution to Track Coach, we will outline and update progress on these Initiatives, as well as additional aspects of the USATF High Performance Plan. It is hoped that this will allow the USATF community of coaches and supporters to have an understanding and an appreciation of the steps being taken by USATF and the USOC to utilize sport science and medicine resources to optimize performance and medal attainment. This report will give the rationale behind and initial outcomes from our second Initiative, which focuses on the distance events.